Overcoming misleading carbon footprints in the financial sector. (3rd July 2022) - Janssen, Artjom; Botzen, Wouter; Dijk, Justin; Duijm, Patty
ABSTRACT: Financial institutions, including pension funds and insurance companies, are key investors in financial markets and important providers of funding to companies. Their investment decisions can steer the transition towards a more sustainable economy and can ensure that sufficient capital is made available for the investments needed to achieve the goals of the Paris Agreement. The development of robust carbon disclosure metrics is key to measuring the sustainability of these institutions' investment portfolios. However, common carbon disclosure metrics are unreliable, since they are prone to macroeconomic effects, such as inflation and exchange rate fluctuations. This becomes relevant when one wants to consider the change in these metrics over time. In this study, we show that when the metrics are adjusted for inflation and exchange rate fluctuations, one can observe the real sustainability improvement over time. We find that sustainability improvements based on existing metrics are notably one-quarter to one-third smaller when adjusted for these effects. Hence, more than one-quarter of the observed 'greening' is 'non-real'; rather it is a consequence of macroeconomic fluctuations. We propose an adjusted metric that is robust to such fluctuations and illustrate its use in evaluating pension and insurance sector investments. Various international organizations, such as the Network of Central Banks and Supervisors for Greening the Financial System (NGFS) and the Task Force for Climate-Related Financial Disclosures (TCFD), are working together to create harmonized climate-related disclosure frameworks. This study aims to contribute to the ongoing work on carbon disclosure by identifying and solving methodological issues that are currently hampering the potential of carbon disclosure metrics, such as Weighted Average Carbon Intensity (WACI). Key policy insights Although carbon disclosure metrics are currently recommended in international reporting standards, presently there is no commonly agreed set of metrics in place. Adjusting relative carbon disclosure metrics for inflation and exchange rate fluctuations makes a significant difference to the level and dynamics of these metrics over time. Adjusting carbon disclosure metrics for inflation and exchange rate effects contributes to establishing a harmonized global framework, which can help steer the transition towards a more sustainable economy and can ensure that sufficient capital is made available for the investments needed to achieve the goals of the Paris Agreement.